Society of consumption: problem of genesis and methodology of social-philosophy analyze - Maksimenko, Sergey V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The author analyzes the genesis of ideas about the phenomenon of the consumer society. Various features of the social structure of the consumer society are revealed. The origins of the phenomenon for determining the essential features of the category of consumerism are explored. The formation of the basic concepts of this social phenomenon as in the Western tradition, in particular the critical, postmodern theory of J. Baudrillard, the theory of the «Consumer revolution» of N. McKendrick, and in the domestic philosophical tradition: the theory of the human-consumer by E. A. Batyuta, the transformation approach of E. A. Samarina, modeling of V. I. Ilyin. Fixed methodological features and heuristic capabilities of these approaches.